A panchromatic electrochromic device composed of Ru(ii)/Fe(ii)-based heterometallo-supramolecular polymer. Issue 25 (5th June 2019) - Hsiao, Li-Yin; Chang, Ting-Hsiang; Lu, Hsin-Che; Wang, Yen-Chun; Lu, Yen-An; Ho, Kuo-Chuan; Higuchi, Masayoshi
Abstract : A panchromatic electrochromic device composed of PolyRuFe and Prussian blue is proposed in this study and the memory effect of PolyRuFe is improved by the incorporation of multi-walled carbon nanotubes. Abstract : An Ru(ii )/Fe(ii )-based heterometallo-supramolecular polymer (PolyRuFe) was synthesized and utilized for the first time as the working electrode in an electrochromic device (ECD). To obtain a panchromatic characteristic, Prussian blue (PB) was selected as the counter electrode owing to its large absorbance change from 600 to 800 nm, which was complementary to the main absorbance change of PolyRuFe from 400 to 600 nm. When switching between −1.3 and 2.2 V, the proposed ECD utilizing the PMMA gel-type electrolyte exhibited transmittance changes (Δ T ) of 52.7, 46.9, and 28.0% at 503, 580, and 690 nm, respectively. Fast response times of less than 0.5 s could be observed for both the coloring and bleaching processes of PolyRuFe/PB ECD at 503 and 580 nm. PolyRuFe/PB ECD also exhibited three-step coloration efficiency and the highest values were 525.1 and 413.6 cm 2 C −1 at 503 and 580 nm, respectively. In addition, the memory effect of the PolyRuFe thin film was enhanced by incorporating multi-walled carbon nanotubes (MWCNTs) into PolyRuFe to form PolyRuFe–MWCNT. The relationship between the memory effect and the mass changes of PolyRuFe and PolyRuFe–MWCNT thin films during the redox reaction was monitored by using a quartz crystal microbalance (QCM). The result suggested that the PolyRuFe–MWCNT thin film offered a better memory effect than bare PolyRuFe due to the adsorption of perchlorate ions on MWCNTs. It is expected that the proposed approach can be applied to other PolyRu electrochromic thin films for improving the long-term stability of the pertinent ECDs.